Factors in Preparing Clients (Readiness) to Carry Out Counseling Activities - Yeni Karneli; Utari Pratiwi; Mudjiran (Journal Of Psychology, Counseling And Education, 2025)
An effective counseling process requires the active involvement of the client in understanding and resolving the problems faced. This readiness includes cognitive, emotional and physical aspects that enable the client to participate optimally in counseling. Several factors, influence client readiness like internal factors include intrinsic motivation, awareness of the need to change, and belief in the effectiveness of counseling, while external factors include social stigma, family support, and community views on counseling. This article shows that clients who have high readiness are more responsive to counselor interventions, thus accelerating the process of desired change. It is important for counselors to build a strong therapeutic relationship and provide education regarding the benefits of counseling. literature study research method, an approach that involves collecting and analyzing literature in the form of books, journals, or magazines relevant to the topic. Although challenges such as client resistance or negative perceptions towards counseling still exist, with the right strategies, client readiness can be improved. This article aims to discuss the implications of client readiness in counseling as well as strategies that can be used by counselors to increase client readiness, so that the counseling process can run effectively and optimally.